Variations Saisonnières Des Paramètres De Reproduction Et Relation Taille-Poids De Auxis thazard (Lacepède, 1800) Capturé Dans Le Golfe De Guinée Par La Flottille Artisanale Ivoirienne - Edoukou Abekan; Diaha N’guessan Constance; Amande Monin Justin; N’guessan Yao; Assan N’dri Florentine; Angui Kouamé Jean Paul; N’da Konan (European Scientific Journal, ESJ, 2017)
In this study, the seasonal variation in sex ratio, macroscopic stages of sexual maturity, gonado-somatic ratio, hepatostatic ratio, condition factor, and size-weight relationship in Auxis thazard from Gulf of Guinea were studied from January to December 2016. Sex ratio observed was in favor of males (1: 0,78; X² observed = 20,16 ˃ theoretical X² = 3,84 ; p ˂ 0,05). The variation of maturity stages associated with GSI, HSI, and K during different seasons of the year showed that this specie spawns throughout the year. Length-weight relationship was W = 0,0039 L 3, 4108 (R2 = 0,93 ; N = 291) for males, W = 0,0036 L 3, 4376 (R2 = 0,91 ; N = 227) for females, and W = 0,004 L 3, 4118 (R2 = 0,92 ; N = 519) for the combined sexes. The b value was significantly higher than the theoretical value of 3 for males (t-test, t = 233,218, p ˂ 0,05), for females (t-test, t = 227,776, p ˂ 0,05), and for all individuals (t-test, t = 315,821, p ˂ 0,05). This situation however indicates a faster increase of the fish in weight rather than in length.